Measuring the success of public-private partnership projects: a conceptual framework - Zayyanu, Muhammad (Journal of Built Environment, Technology and Engineering (JBETE), 2017)
The increasing reliance on public-private partnerships in the provision of infrastructure and services is well documented. However, despite an increasing reliance on public-private partnerships, the performance measurement of PPP projects is less clear in the normative literature. While assessment of success in traditional procurement approaches is relatively straightforward, PPPs, due to their multifarious nature, require more rigour in establishing the success factors and evaluating the extent of their contribution to the success of PPP projects. Using Structural Equation Modelling (SEM) approach, this paper develops a conceptual framework for assessing the success of PPP projects. The authors contend that the proposed framework should assist PPP stakeholders in evaluating the performance of PPP projects.